Frequency and Pattern of Presentation of Different Types of TMJ Ankylosis in Patients Presenting to Nisthar Institute of Dentistry, Multan - Sidra Tul Muntaha, Muhammad Fishan, Asif Nazir, Inqlab Fareed, Nasir Abbas, Safura Hashmi (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Temporomandibular joint (TMJ) ankylosis is a disorder where the temporomandibular joint, which joins the lower jaw to the skull, fuses or becomes "ankylosed." This can result in pain, difficulty opening the mouth, and other symptoms as a result of an injury, infection, or other factors. TMJ ankylosis can be treated with surgery, medication, and physical therapy. Arthrocentesis, arthroscopy, and open-joint surgery are surgical options. This retrospective study sought to examine the temporomandibular joint (TMJ) ankylosis pattern and its underlying causes in patients who had received treatment at Multan’s Nisthar Institute of Dentistry. Methods: From 2018 to 2022, Nishtar Institute of Dentistry, Multan treated patients with temporomandibular joint ankylosis for 4 years. All patients whose records were sufficiently complete were analyzed in this research. Demographic data, the cause and pattern of ankylosis, the interval between the injury and therapy, simultaneous facial lacerations, remnant dislocation, a previous pedicle method, mouth opening prior to and following ankylosis treatment, health issues, the follow-up period, and physical therapy prior to and following ankylosis treatment are all included in the information. Results: Out of 32 patients with 45 afflicted joints and a mean ± standard deviation age of 29.90 ± 17.08 years, 25 (78%) occurrences of temporomandibular joint ankylosis were attributed to trauma (mainly between 20 and 29 years old). Bilateral participation outweighed unilateral involvement 13 to 9 and males outnumbered women 23 to 9. Restricted mouth opening was the patient’s primary complaint the majority of the time (n=24, or 75%). The temporomandibular joint was completely ankylosed in 24 individuals. Prior to surgery, the mean maximum mouth openness was 0.95 ± 0.45 cm; however, it dramatically elevated to 4.50 ± 0.50 cm (p-value 0.001) following surgery. Conclusions: This research found that the most frequent complication of temporomandibular joint ankylosis among the participants it looked at was trauma. The patient’s limited mouth opening was their most frequent primary complaint. Additionally, this study’s findings revealed that men are more likely than women to develop TMJ ankylosis and that these patients’ TMJ functions can be significantly improved through the surgery. Keywords: temporomandibular, TMJ, temporomandibular joint